Higher Order Thinking Skill (HOTS) Students in Indonesia and Saudi Arabia (Comparative Study of Assessment Application in Schools) - Ayuningtias Yarun; Moch. Zainal Arifin Hasan; Syahri Syahri; Markus Markus (Journal of Contemporary Islamic Education, 2023)
In fact, the HOTS assessment is intended for students who are capable of higher-order thinking. However, the reality that occurs in Indonesia and Saudi Arabia in international competition, such as the PISA ranking, is still at level 1. This study aims to compare the application of HOTS assessments in schools between Indonesia and Saudi Arabia. This study uses a systematic review through review of students' Higher Order Thinking Skill (HOTS) journals in Indonesia and Saudi Arabia. The study's results found (1) The application of HOTS assessments in Indonesia is more of an assessment in the form of questions and reading literacy activities. Meanwhile, in Saudi Arabia, to improve students' higher-order thinking skills, they must pay more attention to learning approaches and strategies. (2) The type of assessment that exists in Indonesia today is the formative assessment to improve the learning process while summative after the learning process ends. Whereas in Saudi Arabia the assessment is more of an evaluation than a test in the realm of summative, formative and computer-assisted assessment. This research is beneficial for student achievement because there are assessment practices that suit student needs. In addition, this comparison can be a reference for further research to find similarities and differences in understanding the application of the assessment.